13th IET International Conference on AC and DC Power Transmission (ACDC 2017) 2017
DOI: 10.1049/cp.2017.0062
|View full text |Cite
|
Sign up to set email alerts
|

VSC-HVDC for Frequency Support (a review)

Abstract: To reduce CO2 emissions produced by electricity generation, conventional fossil fuel power plants are being decommissioned. Renewable energy sources (RES) and interconnectors are replacing these old power plants but have different operating characteristics. A key concern as the conventional fossil fuel power plants are displaced is the reduction in system inertia. A reduction in system inertia will require faster control schemes to be implemented to prevent frequency and rate of change of frequency (ROCOF) lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Among articles giving overviews of FR techniques for the VSC-HVDC, reference [25] introduced some coordinated FR strategies by means of discussion, but does not include the control diagrams of these methods. Reference [26] summarized the inertial control, droop control, proportional integral (PI)-based control, and their modified controllers for FR in a VSC-HVDC system. The authors in [27] proposed a classification of inertia control strategies for the VSC-HVDC based on the type of synchronization with the grid and the coordination between other generation sources: synchronized with and without phase-locked-loop (PLL), centralized control, and distributed control.…”
Section: Introductionmentioning
confidence: 99%
“…Among articles giving overviews of FR techniques for the VSC-HVDC, reference [25] introduced some coordinated FR strategies by means of discussion, but does not include the control diagrams of these methods. Reference [26] summarized the inertial control, droop control, proportional integral (PI)-based control, and their modified controllers for FR in a VSC-HVDC system. The authors in [27] proposed a classification of inertia control strategies for the VSC-HVDC based on the type of synchronization with the grid and the coordination between other generation sources: synchronized with and without phase-locked-loop (PLL), centralized control, and distributed control.…”
Section: Introductionmentioning
confidence: 99%
“…By taking advantage of the ability of power electronics to respond fast using a P-f droop characteristic for HVDC-VSC interconnections becomes a feasible solution to provide frequency support in AC systems with low inertia. It has been demonstrated that this is an efficient approach for reducing the maximum frequency deviation in such systems [7], [8]. In [7], a review of supplementary local control strategies for VSC-HVDC for low-inertia and islanded systems is presented.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this is an efficient approach for reducing the maximum frequency deviation in such systems [7], [8]. In [7], a review of supplementary local control strategies for VSC-HVDC for low-inertia and islanded systems is presented. In [9], In [8], a frequency control scheme for VSCs, which are part of an HVDC grid connecting asynchronous AC systems, is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many references have investigated the use of conventional VSC‐HVDC to provide frequency support for the AC system [5]. Junyent et al .…”
Section: Introductionmentioning
confidence: 99%